Effectiveness of adherence to nutritional therapy in type 2 diabetics on hemodialysis - Salazar, Patricio; Anderson, Hazel (Revista Gregoriana de Ciencias de la Salud, 2025)
Type 2 diabetes is one of the leading causes of chronic kidney disease, and its treatment through hemodialysis requires strict adherence to nutritional therapy. This study evaluated anthropometric and biochemical parameters, as well as the degree of dietary adherence, in 87 patients with diabetic nephropathy undergoing hemodialysis in Ecuador. Serial measurements were conducted over a six-month period, and the DDFQ questionnaire was used to assess adherence to dietary and fluid restrictions. Significant sex-based differences were observed in waist, arm, and calf circumferences (p